2011
DOI: 10.1063/1.3531989
|View full text |Cite
|
Sign up to set email alerts
|

Thickness dependence of the effective damping in epitaxial Fe3O4/MgO thin films

Abstract: The precessional magnetization dynamics of high quality epitaxial magnetite ͑Fe 3 O 4 ͒ thin films growth on MgO are investigated by inductive magnetization dynamic measurements in time and frequency domain. An upper bound for the intrinsic Gilbert damping parameter of ␣ 0 = 0.037Ϯ 0.001 is derived, which is significantly lower than previously reported for epitaxial Fe 3 O 4 on GaAs. With increasing film thickness from 5 up to 100 nm a strong increase in the effective damping up to 0.2 is observed which cannot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…27 For thin films, there is a clear trend visible for a to decrease with decreasing size 21-23 and in Ref. 22, an upper limit for a in iron oxide thin films of 0.0365 is found. We argue that in MNP this value is expected to be even significantly smaller because of the nanoscale dimensions in every direction.…”
Section: Resultsmentioning
confidence: 87%
“…27 For thin films, there is a clear trend visible for a to decrease with decreasing size 21-23 and in Ref. 22, an upper limit for a in iron oxide thin films of 0.0365 is found. We argue that in MNP this value is expected to be even significantly smaller because of the nanoscale dimensions in every direction.…”
Section: Resultsmentioning
confidence: 87%
“…This result is one order of magnitude smaller than the reported values for other similar systems, such as YIG/Pt thin films. 6,25 The difference can be explained considering magnetite thin films' higher damping constant than YIG, 6,26 since K is considered to scale as the inverse of the damping constant. 27 Previous studies 11 have shown that SSE is suppressed at high magnetic fields, suggesting that low frequency magnons are important in SSE.…”
mentioning
confidence: 99%
“…On the other hand, the dynamic magnetic properties such as magnetic anisotropy and magnetization damping of Zn x Fe 3x O 4 thin films are less reported may be related to the difficulty of the ultrafast dynamic characterization. Fe 3 O 4 thin film has large Gilbert damping and weak magnetic anisotropy in nature [10,11]. Zn dopant in Zn x Fe 3x O 4 thin film can induce extrinsic damping and additional magnetic anisotropy.…”
Section: Introductionmentioning
confidence: 99%